Sex related haematological variations in Himalayan golden mahseer, Torputitora (Ham.) - Kapila, R; Kapila, S; Basade, Y (Indian Journal of Fisheries, 2011)
With a view to monitor the health status of the endangered golden mahseer foreffective conservation measures, the haematological investigations were carried outon blood collected from the heart of ripe specimens netted out from Bhimtal lakeduring spawning season. The sex related studies indicated that the males hadstatistically significant (p